Implementasi Kebijakan Bantuan Langsung Tunai Di Desa Sidomulyo Kota Batu Berdasarkan Analisis Van Meter Dan Van Horn - Amma, Gisela Mburu; Bagus, Nanang; Suprojo, Agung (Lenvari: Journal of Social Science, 2024)
Direct Cash Assistance (BLT) is direct assistance in the form of a certain amount of cash for households that really need it, namely households that are included in the very poor category. This program was launched by the government as social protection for the poor to reduce the negative impact of The policy of adjusting compensation to reduce fuel subsidies is to help poor people meet their basic needs. The objectives of this research are (1) to find out the implementation of the Direct Cash Assistance program policy in the Sidomulyo Village area, Batu District, Batu City. (2) to find out what are the supporting and inhibiting factors from the government of the village government in implementing the Direct Cash Assistance policy in Sidomulyo area, Batu District, Batu City. The type of research used by researchers is descriptive research with a qualitative research approach, the focus of the research is (1) Implementation of public policy (2) Direct Cash Assistance Program in Sidomulyo Village (3) Analysis of Van Meter and Van Horn so that the informants in this research are (1 ) Head of Sidomulyo Village, as general person in charge of the area. (2) Village Secretary as person in charge of administration (3) Head of the People's Welfare Section as person in charge of the Direct Cash Assistance Program in Sidomulyo Village.